Zinc Barium Oxalate Crystals Grown by Gel Method: A Spectroscopic and Thermal Studies - Mangala M. Sanjeevannanavar; N. Jagannatha; P. S. Rohith (Challenges and Advances in Chemical Science Vol. 8, 2022)
The silica hydrogel technique was used to successfully grow zinc mixed barium oxalate (ZnBaO) crystals in this paper. The optimum conditions were determined by varying parameters such as the specific gravity of Sodium Meta Silicate (SMS), the concentration of the oxalic acid (C2H2O4.2H2O) solution, the pH of the gel, the gel setting time, the concentration of reactants such as zinc chloride (ZnCl2) and barium chloride (BaCl2.2H2O) and so on. Characterization with a Field Emission Scanning Electron Microscope (FESEM) reveals the presence of various layers in the grown crystals. Energy Dispersive X-ray Analysis (EDAX). Was used to investigate elemental analysis. It determines the elemental percentage composition of the grown crystals. The EDAX analysis confirms that the grown crystal contains Zn2+, Ba2+, C, and O elements. The vibrational analysis of grown crystals identified by FTIR and laser Raman spectroscopy reveals the presence of functional groups such as the O-H band, C-H band, C=O, C-C bands, and metal oxide bands. The UV-Visible spectrum analysis reveals optical constants such as the energy bandgap, absorption coefficient, refractive index, reflectance, electrical polarizability, and cutoff wavelength of the grown crystal. These constants are used to characterize materials that are used in a variety of applications such as the fabrication of opto-electronic devices. Thermal stability of ZnBaO crystals were studied by TGA, DSC and DSC which reveals the chemical process involved in the decomposition.